Sustained viral response and relapse after discontinuation of oral antiviral drugs in HBeAg-positive patients with chronic hepatitis B infection - Sun, Fangfang; Li, Zhenhua; Hu, Leiping; Deng, Wen; Jiang, Tingting; Wang, Shiyu; Bi, Xiaoyue; Lu, Huihui; Yang, Liu; Lin, Yanjie; Zeng, Zhan; Shen, Ge; et al. (Frontiers in Immunology, 2022)
Objective To investigate the sustained virological response and relapse in chronic hepatitis B(CHB) patients with hepatitis B e antigen (HBeAg) positive after stopping oral antiviral drugs, and to monitor the disease progression and the incidence of adverse events such as liver cirrhosis and hepatocellular carcinoma. Methods This is a prospective observational study. Patients who continued nucleos(t)ide analogue (NA) treatment after achieving HBeAg seroconversion for more than 3 years were enrolled. After signing the informed consent form, patients stopped NA treatment and received follow-up. During the follow-up, the antiviral treatment information of the patients was collected, and the follow-up observation was carried out every 3 months since the enrollment. We monitored the virological indexes, liver and kidney function, serology and liver imaging during follow-up. The purpose of this study was to identify the sustained virological response rate, viral relapse rate, clinical relapse rate and the related factors after drug withdrawal. Results A total of 82 patients were enrolled, including 42 males (51.22%) and 40 females (48.78%), with a median age of 34.00 (31.00, 37.25) years. All enrolled patients were followed up for 1 year. At the end of the follow-up, 36.59% (30 / 82) of patients had sustained virological response, 63.41% (52 / 82) of patients had HBV DNA reactivation, 17.07% (14 / 82) of patients had clinical relapse, and 10.98% (9 / 82) of patients had HBeAg reversion. There were no adverse events such as liver cirrhosis and hepatocellular carcinoma. The median level of HBsAg in patients with sustained virological response was lower than that in patients with HBV DNA reactivation (2.92 vs.3.18 log10IU/ ml, Z=-1.492/P=0.136), and the median level of baseline HBsAg in patients with HBV DNA reactivation was lower than that in patients with clinical relapse (3.01 vs.3.45 log10IU/ml, Z=-1.795/P=0.073), but the difference was not significant. Conclusion The sustained virological response rate of HBeAg positive CHB patients after stopping oral antiviral treatment is lower, and it is more common in patients with lower HBsAg levels. Patients still need to be closely monitored after stopping NA therapy.